Laminin is structurally conserved in the sea urchin basal lamina - McCarthy, Robert A. (1987)
The extracellular matrix is involved in the regulation of differentiation and morphogenesis. Here we report the identification of a sea urchin embryonic extracellular matrix protein by means of a monoclonal antibody BL1 (Mab BL1) and the isolation of the protein from basal lamina preparations. In paraffin sections of fixed embryos, the antibody can be detected on the basal surfaces of cells after the blastula stage. Immunoprecipitation from embryo lysates and salt extracts of metabolically labeled basal lamina preparations demonstrates that the basal lamina antigen is a large mol. wt protein of approximate mol. wt 10(6) which consists of disulfide-linked subunits of mol. wts ˜480 000 and 260 000. Electron microscopic images show that the Mab BL1 basal lamina antigen is structurally related to the vertebrate extracellular matrix protein laminin.